Indigenous nation building for environmental futures: Murrundi flows through Ngarrindjeri country. Issue 3 (3rd July 2019) - Hemming, Steve; Rigney, Daryle; Bignall, Simone; Berg, Shaun; Rigney, Grant
ABSTRACT: In 2015, the Ngarrindjeri Nation in concert with the South Australian government won the Australian River prize for best practice in water management, after leading the development of a co-management approach to the Coorong, Lower Lakes and Murray Mouth (CLLMM) region during the Australian Millennium drought crisis. The purpose of this article is to explain why the prize-winning advances in water management in this region are an outcome of a strategic political process of Indigenous Nation (re)building, pursued by Ngarrindjeri leaders with the ongoing support of a formal research program focussed on Aboriginal governance. The primary insight revealed by the research is that Indigenous contributions to successful environmental management are not best conceived in terms of the protection of 'cultural flows' – as is suggested by much of the literature in the field – but instead should be understood primarily in political terms. Like other Indigenous Nations, Ngarrindjeri consider they have an inherent and sovereign right to enjoy, use and protect the flow of water through their Country. Ngarrindjeri have effectively articulated their sovereign Aboriginal environmental rights and have successfully negotiated these rights with the South Australian state by producing targeted legal and political innovations that enable shared authority in the co-development of natural resource management policy. The article argues that Indigenous Nation (re)building and self-governance has positive implications for the development of best practice models of land and water management, both in Australia and internationally.